Situation Report: Bulgaria, 11 November 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Todor Zhivkov Attends Polish Party Congress Celebration of Anniversary of October Revolution Warsaw Pact Chief of Staff in Bulgaria Politburo Advocates Convocation of International Communist Conference Information Media Report Anti-Soviet Demonstration in Prague Reaction to US Election Indian CP Delegation in Bulgaria Ideological Conference of Scientists and Technologists Bulgarian Orthodox Church Adopts New Calendar